Integration and Identity: A Project towards Social Cohesion - Ares Mateos, Alberto (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The construction of identity is a vital constituent element in the development of individuals and groups. In our current globalized and diverse world, this element takes on a nuclear relevance, more if possible, from a viewpoint of migratory flows and social integration. It is in daily life that many of the identity dynamics are played, in which processes of personal and collective identity, more static and dynamic tendencies are intertwined. The objective of this work is to provide light to integration and social cohesion models from the processes of identity construction, in dialogue with the mixed integration model (MIM). To this end, the dialogue between Segundo’s model of majority and minority behaviors, Sen’s capability approach, the classic models of integration of immigrants, Castell's model of construction of identities, as well as the empirical study by P. Norris, has been very enriching.
Keywords: identity; integration; migration; social cohesion; globalization